Crisis in a Cup: Managing the Mie Sedaap Recall and Rebuilding Trust - Abdullah, Nur Nabilah; Ramdzan Ali, Al Amirul Eimer; Ramli, Mohd Safwan (IIUM Journal of Case Studies in Management, 2024)
This paper analyses the recall of two products from the Indonesian instant noodle brand Mie Sedaap. This recall followed the discovery by food safety regulators in Hong Kong and Singapore of the Korean Spicy Chicken and Korean Spicy Soup’s prohibited chemical, ethylene oxide. The incident resulted in recalls in both countries between September and October 2022. Being aware of the fact that the adverse consequences were detrimental for the business, the present case study will discuss the ways, in which the Mie Sedaap brand acted in relation to the reputation management when the product was recalled and the ways, in which the company ensured the customers and other stakeholders that their trust was still valued by the company. Moreover, the discussion will entail the integration of some of the SDG aspects namely; good health and wellbeing (SDG 3), responsible consumption and production (SDG 12), and the partnerships for the goals (SDG 17) to analyse the overall effects and the response measures in containing food safety and sustainability issues.